Fatal pneumonia in a patient with Kearns-Sayre syndrome case report and literature review - Zhang, Jiaqi; Song, Ziqin; Zhou, Huimin; Zhou, Yaru; Wang, Shuchang (Frontiers in Medicine, 2025)
Kearns-Sayre syndrome is a mitochondrial DNA deletion disorder, classically characterized by a triad of onset before the age of 20, pigmentary retinopathy, and chronic progressive external ophthalmoplegia (CPEO). The condition is frequently associated with third-degree atrioventricular block, endocrine dysfunction, and short stature. Here, we report a case of KSS presenting with a progressive clinical course that began at birth with ptosis and later developed type 1 diabetes, hypopituitarism, and third-degree atrioventricular block. Genetic analysis of a urine sample revealed a large-scale mitochondrial DNA deletion, confirming the diagnosis of KSS. The patient ultimately died from severe pneumonia precipitated by COVID-19 infection.